Women's knowledge and attitudes regarding alcohol consumption in pregnancy: a national survey - Peadon, E.; Payne, J.; Henley, N.; D'antoine, Heather; Bartu, Anne; O'Leary, C.; Bower, C.; Elliott, E. (Biomed Central, 2010)
Background. Alcohol exposure in pregnancy is a common and modifiable risk factor for poor pregnancy and child outcomes. Alcohol exposure in pregnancy can cause a range of physical and neurodevelopmental problems in the child including the Fetal Alcohol Spectrum Disorders (FASD). In order to improve prevention strategies, we sought to describe the knowledge and attitudes of women of childbearing age regarding alcohol consumption during pregnancy and its effects on the fetus.Methods. We conducted a national cross-sectional survey via computer assisted telephone interview of 1103 Australian women aged 18 to 45 years. Participants were randomly selected from the Electronic White Pages. Pregnant women were not eligible to participate. Quotas were set for age groups and a minimum of 100 participants per state to ensure a national sample reflecting the population. The questionnaire was based on a Health Canada survey with additional questions constructed by the investigators. Descriptive statistics were calculated and logistic regression analyses were used to assess associations with participants' knowledge and attitudes.Results. Of women surveyed, 61.5% had heard about effects of alcohol on the fetus and 55.3% had heard of Fetal Alcohol Syndrome. Although 92.7% agreed alcohol can affect the unborn child, 16.2% did not agree that the disabilities could be lifelong. Most women agreed that pregnant women should not drink alcohol (80.2%) and 79.2% reported having negative feelings towards pregnant women drinking alcohol. Women with higher education levels were more likely to know the effects of alcohol consumption in pregnancy (adjusted OR 5.62; 95% CI 3.20 to 9.87) but education level and knowledge were not associated with attitude.Conclusions. There was a disjunction between knowledge and attitudes towards alcohol consumption in pregnancy. These findings will assist in developing effective health promotion campaigns to reduce fetal alcohol exposure and subsequent fetal damage.